Energy efficiency on data centre Universiti Pendidikan Sultan Idris using internet of things (IOT) for smart cooling system / Kamil Mohamed - Mohamed, Kamil (2019)
The data centre is a facility that consumes a lot of energy and electricity, where it stores the critical data and integrated systems of the user. Other than electricity consumption, air conditioning system is very important to cover the servers, network switches and etc. from the heats. Heat propagation can increase the temperature and causes damage to rack servers, where protection of the system and prolonging their life by cooling the inherent devices is of crucial importance. This research is to implement an IoT in the data centre, UPSI. Therefore, by using the main component such as temperature & humidity sensor DHT22 to collect data. Then, the processed data transmitted through ESP8266EX wireless transceiver module to send data to the cloud. Finally, displaying the results of communication on I2C OLED Module-Blue. In addition, in order to let its display on monitoring based using web-based ThingSpeak.com and Matlab Analytical Tools to analyse the data. This is the best practice to implement an IoT as a new environment in the working place and the approach will enable green cloud computing environment and efficient utilization of energy at data centres UPSI. Comprehensive evaluation, it is a kind of environmental conditions monitoring programme which is low power consumption, low cost, in real-time and remotely.